Interest in using patient portals among adolescents in mental health care - a cross-sectional study - Martine Stecher Nielsen; Aslak Steinsbekk; Torunn Hatlen Nøst (BMC, 2023)
Abstract Introduction Adolescents in mental health care may benefit from using patient portals to access personalised information about their health and treatment. While no studies have considered the interest in using patient portals among adolescents in mental health care, factors such as patient activation, self-reported health, depressive symptoms, diagnosis, healthcare utilisation, and eHealth literacy have been found to be associated with interest in and use of patient portals in other patient groups. Therefore, the aim was to explore the associations between interest in using patient portals and patient activation, self-reported health, depressive symptoms, diagnosis, healthcare utilisation and eHealth literacy among adolescents in specialist mental health care. Methods A cross-sectional study among adolescents between 12 and 18 years of age receiving or having received treatment at four different specialist child and adolescent mental healthcare services across Norway. The adolescents´ answers to the questionnaire were linked to data on their healthcare utilisation and ICD-10 diagnoses from the Norwegian Patient Registry. The data were analysed using descriptive statistics and bivariate tests. Results The 53 adolescents who participated, had a mean age of 15 years and 68% of them identified as female. Two out of three (64%) were interested in using patient portals. Most of the factors were not associated with interest in using patient portals. However, adolescents with mental and behavioural disorders (F diagnoses, 75% interested) were more interested in using patient portals compared to those with symptoms and signs involving cognition, perception, emotional state, and behaviour (R diagnoses, 31% interested). Conclusion Except for mental health diagnosis, this study did not identify any specific factors likely to impact patient portal interest among adolescents in specialist mental health care.